2021
DOI: 10.1093/europace/euab125
|View full text |Cite
|
Sign up to set email alerts
|

Effective termination of atrial fibrillation by SK channel inhibition is associated with a sudden organization of fibrillatory conduction

Abstract: Aims Pharmacological termination of atrial fibrillation (AF) remains a challenge due to limited efficacy and potential ventricular proarrhythmic effects of antiarrhythmic drugs. SK channels are proposed as atrial-specific targets in the treatment of AF. Here, we investigated the effects of the new SK channel inhibitor AP14145. Methods and results Eight goats were implanted with pericardial electrodes for induction of AF (30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
1
17
0
1
Order By: Relevance
“…Several SK-channel inhibitors have demonstrated pronounced antiarrhythmic potential in large animal models, both for acute cardioversion and for prevention of AF reinduction, suggesting a potential for SK-channel inhibition in rhythm control of patients with AF. 7,[9][10][11][12][13] Ventricular effective refractory period is largely unchanged by SK-channel inhibition in most large animal models, therefore, atrial selectivity is likely a beneficial characteristic of I SK blockers. [11][12][13]16 AF is associated with pronounced electrical, structural and Ca 2+ -handling remodeling (reviewed in [59][60][61] ).…”
Section: Potential Significance Of Our Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several SK-channel inhibitors have demonstrated pronounced antiarrhythmic potential in large animal models, both for acute cardioversion and for prevention of AF reinduction, suggesting a potential for SK-channel inhibition in rhythm control of patients with AF. 7,[9][10][11][12][13] Ventricular effective refractory period is largely unchanged by SK-channel inhibition in most large animal models, therefore, atrial selectivity is likely a beneficial characteristic of I SK blockers. [11][12][13]16 AF is associated with pronounced electrical, structural and Ca 2+ -handling remodeling (reviewed in [59][60][61] ).…”
Section: Potential Significance Of Our Observationsmentioning
confidence: 99%
“…6 SK-channel expression and current (I SK ) are upregulated in several animal models of AF, including dogs with 7-days of electrically maintained AF 7 and rabbits with 3-hour intermittent atrial-burst pacing. 8 SK-channel inhibitors prolong atrial repolarization, promote AF-termination in rats, 9 dogs, 7 goats, 10 horses, 11 and pigs 12,13 and reduce the likelihood of subsequent AF-reinduction. 13 Moreover, SK-channel inhibition in pigs can successfully terminate more persistent forms of AF that are resistant to cardioversion by vernakalant, 13 an AAD clinically approved in Europe and several other jurisdictions, suggesting a robust antiarrhythmic efficacy in large animals with remodeled atria.…”
mentioning
confidence: 99%
“…The authors found that AP14145 produced dose-dependent prolongation of AF cycle length and increased the effective refractory period of atrial impulses [102]. Interestingly, atrial conduction velocity in AF following AP14145 treatment remained unchanged until the final seconds before AF termination, where sudden organization of fibrillatory conduction occurred prior to AF cardioversion [102].…”
Section: Pharmacologic Modulation Of Sk Channels In Afmentioning
confidence: 99%
“…In a recent study, Gatta et al conducted a detailed examination of the effects of SK channel inhibitor AP14145 on goat hearts induced to AF after 30 days of burst-pacing stimulation delivered by pericardial electrodes implanted above the left atria [102]. The authors found that AP14145 produced dose-dependent prolongation of AF cycle length and increased the effective refractory period of atrial impulses [102].…”
Section: Pharmacologic Modulation Of Sk Channels In Afmentioning
confidence: 99%
See 1 more Smart Citation